Quality changes during thermal processing of two mixed formulas of fruits and vegetables pulps - Gonçalves, Elsa M.; Raposo, Isa; Pinheiro, Joaquina; Alegria, Carla; Moldão, Margarida; Abreu, Marta (Emirates Journal of Food and Agriculture, 2020)
The present work aimed to evaluate, through thermal degradation kinetics (80 °C to 98 °C in time intervals of 0.5 to 25 min), the effects of different thermal treatments on the biochemical, physicochemical, sensory and microbiological parameters of two mixed fruit and vegetable pulps, a yellow and a red one. The evaluated fruit and vegetable pulps resulted from the mixture of different fruits and vegetables proportions (pineapple, beetroot, strawberry and lemon juice) added to a 50% (p/p) pear-based pulp to maximize their bioactivity, physicochemical stability and sensorial acceptance. Evaluated quality parameters included the determination of peroxidase activity (POD), pH, soluble solids content (SSC), total phenolic content (TPC), CIELab colour, sensory evaluation (colour, taste and aroma) and total mesophilic aerobic counts (TAPC). Regarding heat treatments optimization for both pulps with lower pH, it was concluded that higher temperature treatments (90 to 98 °C) applied over a shorter time (less than 5 min) were more effective to inactivate POD, to reduce the initial microbial load (>2 log10 cycles) and to maximize sensorial attributes. In both mix pulps, total phenolic content (TPC) was not significantly influenced by the different applied time-temperature binomials. From the degradation kinetic models and as an example, it was possible to conclude that POD followed a 1st order kinetic, where the temperature effect was well fitted to the Arrhenius equation. The results allowed to obtain optimized time-temperature binomials for each pulp to simultaneously achieve POD enzyme inactivation, microbial reduction, and maximization of quality parameters relatively to fresh pulps, 90 °C/5 min and 98 °C/2.5 min, for the yellow pulp and red pulp, respectively.